The cellist [compact disc, unabridged] : a novel - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2021)
After the poisoning of a Russian billionaire, Gabriel Allon travels across Europe and finds himself in the reach of a virtuoso musician who may be able to help uncover the truth about his friend's death.